Ang dyip ni Mang Tomas - Gojo Cruz, Genaro R.; Palomo, Anthony E.; Abad, Heidi Emily Eusebio (Quezon City : CANVAS, 2009)
"Tatay never failed to take care of our old jeepney, and we would not have traded it even for the most expensive car around. This jeepney was our lucky charm, he once told me. I had always wondered why... "--Cover.
Keywords: Children's stories, Filipino; Electronic Books